Minimum wages in concentrated labor markets - Martin Popp (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Economists increasingly refer to monopsony power to reconcile the absence of negativeemployment effects of minimum wages with theory. However, systematic evidence for themonopsony argument is scarce. In this paper, I perform a comprehensive test of monop-sony theory by using labor market concentration as a proxy for monopsony power. Labormarket concentration turns out substantial in Germany. Absent wage floors, a 10 per-cent increase in labor market concentration makes firms reduce wages by 0.5 percentand employment by 1.6 percent, reflecting monopsonistic exploitation. In line with per-fect competition, sectoral minimum wages lead to negative employment effects in slightlyconcentrated labor markets. This effect weakens with increasing concentration and, ulti-mately, becomes positive in highly concentrated or monopsonistic markets. Overall, theresults lend empirical support to the monopsony argument, implying that conventionalminimum wage effects on employment conceal heterogeneity across market forms.
Keywords: J42; J38; D41; J23; 330; minimum wage; labor market concentration; monopsony; labor demand